A master-slave control strategy of the multi-modular SMR. (April 2019) - Wei, Xinyu; Qing, Junyan; Wan, Jiashuang; Wang, Pengfei; Zhao, Fuyu
Highlights: A MSMR system with reactor core, OTSG, and steam header is modeled. A MSMR system simulation platform with 4 modules is built in Simulink environment. A master-slave control strategy is developed for steam flow sharing control of MSMR systems. Abstract: Small modular reactor (SMR) is a type of advanced reactor depending on its inherent safety, good economic performance, and multipurpose. SMR always adopts the multi-modular layout, which uses several nuclear steam supply systems (NSSSs) to supply steam to a common steam header. A pressurized water reactor (PWR) type multi-modular SMR (MSMR) system is studied in this paper. Due to the operation demands of continuity and flexibility during load following, a proper control strategy and operation scheme of the MSMR must be investigated. A master-slave control strategy is proposed for steam flow sharing control of the MSMR systems. Under the proposed control strategy, one of the NSSS modules is selected as the master control channel, and its feed water flow rate is regulated using the steam header pressure error. The remaining NSSS modules are treated as the slave channels. The feed water flow rate of the master channel is utilized to slave the other channels, which are flow-controlled. Three operation schemes are set according to different operation demands.(1) Equilibrium Scheme (EquS), in which every module undertakes the same load during the load following operation.(2) Non-equilibrium Scheme (NEquS), in which every module undertakes the different loads during the load following operation. This operation scheme manages more modules operate at full power to ensure its economy and operation simplicity.(3) Constant Output Scheme (ConS), which is mainly used during refueling or maintenance process. When one module is disturbed, other modules undertake its load to ensure the total power output constant. Based on these schemes, four typical operation cases are defined and simulated. Through the analysis of the simulation results, the suitable operation conditions for these operation schemes are suggested, and the relevant control strategy is verified.